Students’ Perception of The Challenges in Comprehending the English Language Listening Test - Sidhu, Parveen Sarjit; Sivaguru, Shobhanambigha (Universitas PGRI Madiun, 2023)
Listening is an essential component of the communication process. Of the four primary components of communication skills—reading, listening, speaking, and writing—it is the most crucial one. Therefore, this study was conducted to investigate the students’ perception of the factors that make it challenging to comprehend the